Analisis Posisi Dasar Teknik Passing Bawah pada Permainan Bola Voli Siswa Putra SMK N 4 Kota Sorong - AJi Suryo Putro, Waskito; Madai, Mesak; Sugiono; Istiyono (Jurnal Muara Olahraga, 2024)
This study aims to determine the relationship between arm strength, leg strength and hand eye coordination with down passing ability in volleyball. The method used in this research is a qualitative method. The population is all male students of SMK Negeri 4 Sorong city class or by practice. The collected data needs to be analyzed descriptively qualitatively. Based on the research results, the following answer was found: From the data, the overall results of this research show that 4 students took the basic lower passing position test, the students who performed the lower passing position "very well" totaled 2 students with a score of 9, for a percentage of (50%), "good" amounted to 2 students with a score of 7% with a percentage (50%)